Auditory Reasoning Skills of Cochlear Implant Users - Aslan, Filiz (J Int Adv Otol, 2019)
OBJECTIVES: This study compared the auditory reasoning skills of school-going children with early and late cochlear implantation and assessed the relationship between auditory reasoning skills, language development, vocabulary knowledge, and communication skills. MATERIALS AND METHODS: In this case series study, 90 pre-lingually deaf children aged 7–10 years were assessed. Children were divided into two groups: early-implanted group with children who received cochlear implants before 3 years of age (mean, 23.45; 12–35 months) and late-implanted group with children implanted after 3 years of age (mean, 50.54; 36–84 months). Tests were performed in the auditory-visual condition. Correlational analyses were used to assess the relationships between daily communication skills, language development performances, vocabulary knowledge, and auditory reasoning skills of both the groups. RESULTS: Auditory reasoning skills were better in the early-implanted group than in the late-implanted group (Mann–Whitney U test=518, p<0.05). Language performances of the early-implanted group were significantly better than those of the late-implanted group (receptive language performances: Mann–Whitney U=522, p<0.05; expressive language performances: Mann–Whitney U=552, p<0.05). Stepwise regression analysis showed that expressive language performances, vocabulary knowledge, and chronological age could predict 82% of the variance. CONCLUSION: Reasoning skills of children with cochlear implants should be supported during the language-learning process.